2003
DOI: 10.1023/a:1022007327077
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and sexual trauma in childhood and adulthood

Abstract: This study evaluates the occurrence of psychopathology among 97 women who (1) experienced sexual abuse in childhood only, (2) were raped in adulthood only, (3) experienced both childhood sexual abuse and rape in adulthood, or (4) experienced no sexual trauma. Women were recruited from advertisements and assessed using the Structured Clinical Interview for DSM-IV (SCID-I/P) and the Modified PTSD Symptom Scale Self-Report. Women who reported sexual trauma were significantly more likely to exhibit psychopathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 9 publications
4
35
0
2
Order By: Relevance
“…Faravelli et al (2004) found that women who had been sexually assaulted were significantly more likely to report an eating disorder compared with women who had not been assaulted. This is supported by the literature reporting the most frequently reported psychiatric consequences of sexual abuse in women are PTSD, mood disorders, substance abuse disorders, eating disorders and sexual disorders (Putnam & Trickett, 1997;Dahl, 1989;Thompson et al, 2003).…”
Section: Post Traumatic Stress Disorder (Ptsd)mentioning
confidence: 55%
“…Faravelli et al (2004) found that women who had been sexually assaulted were significantly more likely to report an eating disorder compared with women who had not been assaulted. This is supported by the literature reporting the most frequently reported psychiatric consequences of sexual abuse in women are PTSD, mood disorders, substance abuse disorders, eating disorders and sexual disorders (Putnam & Trickett, 1997;Dahl, 1989;Thompson et al, 2003).…”
Section: Post Traumatic Stress Disorder (Ptsd)mentioning
confidence: 55%
“…One of these was the outcome of substance abuse after sexual assault (Kaukinen & DeMaris, 2005;Reviere et al, 2007;Thompson et al, 2003;Ullman et al, 2006). Sexually assaulted women who had histories of childhood sexual abuse were found to be significantly more likely to have substance abuse issues.…”
Section: C) Individual Factors: a Focus On Age And Prior Illnessmentioning
confidence: 99%
“…Esta es una variable mediadora en el desarrollo de la psicopatología derivada de experiencias negativas como las del abuso sexual. 24 Mediante el afrontamiento directo la víctima puede reducir el estrés 1 y con ello detener el desarrollo de la patología. Los resultados encontrados sugieren la importancia de investigar e incorporar en las intervenciones para la prevención y la atención del abuso sexual infantil talleres para el desarrollo de habilidades cognitivo conductuales de control directo del problema del abuso o de su prevención en la minoría de edad.…”
Section: Discussionunclassified